Teaching Digital Systems in the Context of the New European Higher Education Area: A Practical Experience - Pardo, X.C.; Martin, M.J.; Sanjurjo, J.; Regueiro, C.V. (IEEE transactions on education, 2009)
This paper describes a practical experience of adapting the teaching of a course in Computer Technology (CT) to the new demands of the European Higher Education Area (EHEA). CT is a core course taught in the first year of the degree program Technical Engineering in Management Computing in the Faculty of Computer Science at the University of A Coruna (UDC), Spain. The contents of this course are mainly devoted to the design of digital systems. The main purpose of the adaptation has been to focus more on students, clearly defining the abilities they will develop during the course and suggesting activities that facilitate the development of those abilities. The aim of this work is to describe how this adaptation was performed, the materials and activities prepared, the difficulties encountered, the goals achieved and the response of students and teachers to these changes.